RELEVANSI KONSEP PENDIDIKAN ISLAM AL-GHAZALI TERHADAP PENDIDIKAN ISLAM KONTEMPORER - Lubis, MelliFera (UIN Sumatera Utara, 2023)
The development agenda of a nation, especially in the field of education, will never stop and be finished. This is because education is an ongoing process, which will always exist and develop according to the dynamics of people's lives. Education plays a very important role in the formation of human identity. Through education, each individual is guided and fostered to realize the ideal society that is aspired to through education. It is not an easy job, along with the development of human life which is increasingly complex, the act of educational and scientific innovation becomes urgent which is of course adapted to the times. The purpose of national education leads to the formation of four aspects, namely, religious aspects, moral aspects, intellectual aspects, and national aspects. All these aspects are realized in order to form a complete and complete human being. At the field level, religious aspects and aspects of morality are wrongly captured by Religious Education. The role of Islamic religious education in achieving the goals of national education is very strategic, because the objectives of Islamic religious education are an integral part of the goals of national education. logistically, that the goals of National Education will be achieved if the goals of Islamic education have been achieved first. The vision of Islamic religious education is a source of values and guidelines in the development and implementation of educational programs in order to help students who have quality, personality, faith, and piety.